Human Dermcidin Protects Mice Against Hepatic Ischemia-Reperfusion–Induced Local and Remote Inflammatory Injury - Qiang, Xiaoling; Li, Jianhua; Zhu, Shu; He, Mingzhu; Chen, Weiqiang; Al-Abed, Yousef; Brenner, Max; Tracey, Kevin J.; Wang, Ping; Wang, Haichao (Frontiers in Immunology, 2022)
Background: Hepatic ischemia and reperfusion (I/R) injury is commonly associated with surgical liver resection or transplantation, and represents a major cause of liver damage and graft failure. Currently, there are no effective therapies to prevent hepatic I/R injury other than ischemic preconditioning and some preventative strategies. Previously, we have revealed the anti-inflammatory activity of a sweat gland-derived peptide, dermcidin (DCD), in macrophage/monocyte cultures. Here, we sought to explore its therapeutic potential and protective mechanisms in a murine model of hepatic I/R. Methods: Male C57BL/6 mice were subjected to hepatic ischemia by clamping the hepatic artery and portal vein for 60 min, which was then removed to initiate reperfusion. At the beginning of reperfusion, 0.2 ml saline control or solution of DCD (0.5 mg/kg BW) or DCD-C34S analog (0.25 or 0.5 mg/kg BW) containing a Cys (C)→Ser (S) substitution at residue 34 was injected via the internal jugular vein. For survival experiments, mice were subjected to additional resection to remove non-ischemic liver lobes, and animal survival was monitored for 10 days. For mechanistic studies, blood and tissue samples were collected at 24 h after the onset of reperfusion, and subjected to measurements of various markers of inflammation and tissue injury by real-time RT-PCR, immunoassays, and histological analysis. Results: Recombinant DCD or DCD-C34S analog conferred a significant protection against lethal hepatic I/R when given intravenously at the beginning of reperfusion. This protection was associated with a significant reduction in hepatic injury, neutrophilic CXC chemokine (Mip-2) expression, neutrophil infiltration, and associated inflammation. Furthermore, the administration of DCD also resulted in a significant attenuation of remote lung inflammatory injury. Mechanistically, DCD interacted with EGFR, a key regulator of liver inflammation, and significantly inhibited hepatic I/R-induced phosphorylation of EGFR and a downstream signaling molecule, AKT. The suppression of EGFR expression by transducing Egfr-specific shRNA plasmid into macrophages abrogated the DCD-mediated inhibition of nitric oxide (NO) production induced by a damage-associated molecular pattern (DAMP), cold-inducible RNA-binding protein, CIRP. Conclusions: The present study suggests that human DCD and its analog may be developed as novel therapeutics to attenuate hepatic I/R-induced inflammatory injury possibly by impairing EGFR signaling.